Thrombolysis, the only Optimally Rapid Reperfusion Treatment - Gurewich, Victor (Journal of Cardiology and Cardiovascular Medicine, 2017)
Thrombolysis with tissue plasminogen activator (tPA) has been plagued by inadequate efficacy and a high risk of intracranial hemorrhage (ICH), which led to its replacement by procedures like percutaneous coronary intervention (PCI) whenever possible. Since this requires hospitalization, it is time-consuming, and compromising salvage of brain tissue and myocardium. Thrombolysis is the only first-line treatment that can provide sufficiently timely treatment for optimal recovery of organ function. However, for this potential to be realized, its efficacy and safety must be significantly improved over the current method. By adopting the sequential, synergistic fibrinolytic paradigm of the endogenous system, already verified by a clinical trial, this becomes possible. The endogenous system’s function is evidenced by the fibrinolytic product D-dimer that is invariably present in blood, and which increases >20-fold in the presence of thromboembolism. This system uses tPA to initiate lysis, which is then completed by the other fibrin-specific activator prourokinase (proUK). Since tPA and proUK in combination are synergistic in fibrinolysis, it helps explain their efficacy at their low endogenous concentrations.